Cover Picture: Solid–Electrolyte Interphase Evolution of Carbon‐Coated Silicon Nanoparticles for Lithium‐Ion Batteries Monitored by Transmission Electron Microscopy and Impedance Spectroscopy (Energy Technol. 7/2015). Issue 7 (7th July 2015) - Van Havenbergh, Kristof; Turner, Stuart; Driesen, Kris; Bridel, Jean‐Sébastien; Van Tendeloo, Gustaaf
Abstract : Uncovering the Solid–Electrolyte Interface: TThe main drawbacks of silicon as the most promising anode material for lithium‐ion batteries (theoretical capacity=3572 mAh g −1 ) are lithiation‐induced volume changes and the continuous formation of a solid–electrolyte interphase (SEI) upon cycling. In the Full Paper by Kristof Van Havenbergh and colleagues from the University of Antwerp and Umicore Research onpage 699, the influence of a thin carbon coating on the surface of silicon nanoparticles is studied with respect to the formation and evolution of the SEI by using electron energy‐loss spectroscopy (EELS) and electrochemical impedance spectroscopy (EIS). The cover picture consists of a false‐color image of surface‐oxidized silicon nanoparticles for Li‐ion battery anodes, showing silicon inblue and oxygen inred, obtained using scanning transmission electron microscopy (TEM) in combination with energy‐dispersive X‐ray spectroscopy (EDX). By combining TEM and EIS studies, the surface evolution of the nanoparticles on a very local scale was connected with device information on the electrode level. A TEM–EELS fingerprint signal of carbonate structures from the SEI was discovered, which can be used to differentiate between the SEI and a graphitic carbon matrix.